Indicadores de sustentabilidade para gestão de resíduos sólidos urbanos - Polaz, Carla Natacha Marcolino (2008)
One way to operationalize the concept of sustainability is through the use of indicators that are useful in planning, monitoring and evaluation steps of Municipal Solid Waste (MSW) policies. They can also help the public managers in setting priorities and goals, providing subsidies for technical decision making. The core objective of this research was to contribute to the development of sustainability indicators for public management of MSW in São Carlos/SP, from the perspective of five dimensions - environmental, economic, social, political and cultural. Based on a prior model proposed by Milanez (2002), the strategy adopted for the indicators adjustment to the São Carlos context was the analysis of the application model process in two consecutive years (2006/2007), followed by the identification of priority problems for the MSW management. For this, managers from two municipal divisions of the São Carlos prefecture, who work in different sectors related to MSW management, were consulted through semi-structured interviews. After the systematization of information obtained from the consultations, an initial proposal of indicators was drawn up. Through a workshop, the first set of indicators was then submitted to some specialists analysis. Both consultation processes (managers and specialists) resulted in the final set, composed of 15 indicators predominantly qualitative, distributed in the five dimensions considered. Of these, seven indicators were kept of the proposed Milanez set, three were adapted from literature and five were drafted from the identification of priorities for the MSW management in São Carlos. For each indicator were characterized the parameters of trend, expressed in three possible conditions: favorable, unfavorable or very unfavorable to sustainability. Since future applications were required to validate this proposal, the results obtained so far showed that the implementing process of a local indicators system should involve the participation of different actors in the selection, review and characterization steps in order to legitimize the effective use of this important management tool. However, the main difference resulting from the adoption of this type of indicator, will be a change in the perception of the general situation of MSW management, in which principles and dimensions of sustainability will be considered.